2009
DOI: 10.1136/thx.2008.098814
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prognostic index for 90-day mortality in patients discharged after admission to hospital for community-acquired pneumonia

Abstract: Background: Although patients admitted to hospital for community-acquired pneumonia (CAP) experience substantial short-term mortality following hospital discharge, few studies have focused on identifying factors that predict mortality after admission to hospital in this population. The objective of this study was to develop and validate a prognostic index for 90-day mortality after hospital discharge among patients with CAP. Results: In the derivation cohort, three factors were independently associated with 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
13
0
2
Order By: Relevance
“…Marrie and Wu 7 found several factors that discriminated between early and late in-hospital mortality. Like Capelastegui et al, 13 they found that baseline functional status was highly associated with later mortality.…”
Section: Resultsmentioning
confidence: 94%
“…Marrie and Wu 7 found several factors that discriminated between early and late in-hospital mortality. Like Capelastegui et al, 13 they found that baseline functional status was highly associated with later mortality.…”
Section: Resultsmentioning
confidence: 94%
“…In a prospective observational study which analyzes factors that predict in-hospital mortality among 3043 patients with CAP who require hospitalization, mortality was 1.4 higher in patients who needed a wheelchair and 4 times greater in bed-ridden patients than in those who did not require any help. 21 Capalastegui et al 22 developed a prognostic index for 90-day mortality after hospital discharge among patients with CAP, they observed that three factors were independently associated with 90-day mortality: pre-illness functional status, co-morbid illnesses and severity on hospital admission. In our geographical area, a multicenter prospective study 18 on patients with CAP, over 70 years and with limited functional capacity was carried out; the authors analyzed whether the place of residence (nursing homes or community) was an independent prognostic factor; they concluded that when the patients' functional capacity was poor, the place of residence was irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…22 All patients who were diagnosed with CAP in the ED during one year were included, thus avoiding any possible selection bias; all the prognostic risk factors for patients with CAP were fully evaluated. However, this study has also several limitations: some patients with CAP are cared by family doctors and may not be referred to hospital, however, these are usually less severe cases of CAP; the rate of admittance to hospital was very high, higher than in other studies, the primary care doctors may have referred to our hospital only patients with severe CAP or with problems in complying with treatment; finally this is a observational study, so we can only suggest an association between poor functional status and mortality in patients with CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Community-acquired pneumonia (CAP) is a cause of substantial and long-term mortality and morbidity, [1][2][3] and the number of patients admitted annually to hospital is increasing. [4][5][6] In recent years controversy has surrounded the prognostic benefit conferred by early antibiotic treatment of CAP on arrival to hospital.…”
Section: Introductionmentioning
confidence: 99%